Stakeholders adopt participatory approach to scale the peste des petits ruminants vaccine in central Mali - Sow, Ahmadou; Kantao, O.; Dara, S.; Bamba, A.; Dione, Michel M. (International Livestock Research Institute, 2025)
In Mali, peste des petits ruminants (PPR) constitutes a major health problem for small ruminants. The difficulty of combating PPR stems from low vaccination coverage, which is mainly due to logistical challenges and limited awareness of farmers about the benefits of vaccination. Using participatory approaches through the establishment of 26 Innovation Platforms (IPs) at commune level in Sikasso, Koutiala, and Ségou regions, 211,893 sheep and goats were vaccinated with the PPR thermotolerant vaccines for the benefit of 10,000 farmers.